DINAMIKA MASYARAKAT KONSUMTIF BALI DALAM UPACARA AGAMA (GEBOKAN PERSPEKTIF EKONOMI) - I Made Sujana (STIE BIITM, 2020)
ABSTRACTThere are 3 (three) economic issues regarding Production, distribution and consumption,and to overcome them must also be from that problem, namely how to produce more andbetter and diverse, and then from the production how to distribute it evenly and thoroughly toconsumers or society and further is how to consume to be more useful and beneficial tosociety. A good and right consumption if consumers can use it effectively means that it isright on target and is fully beneficial and this can improve economic growth and people'swelfare will be better, but if used consumptive or even excessive consumerism will be able toreduce economic growth. The basic framework of the teachings of Hinduism, especially inBali is divided into 3 (three) parts, namely Tattwa (philosophy), Susila (ethics) andCeremony (yadnya) all are integrated and related to one another. Tattwa means